2008
DOI: 10.1165/rcmb.2007-0432oc
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-Induced Activation of AMP Kinase in the Lung Requires Dystroglycan

Abstract: Lung cells are exposed to cyclic stretch during normal respiration and during positive pressure mechanical ventilation administered to support gas exchange. Dystroglycan is a ubiquitously expressed matrix receptor that is required for normal basement membrane formation during embryogenesis and for maintaining the function of skeletal muscle myocytes and neurons where it links cells to matrix. We previously reported that equibiaxial stretch of primary alveolar epithelial cells activated the MAP kinase pathway E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 40 publications
(53 reference statements)
0
31
0
1
Order By: Relevance
“…Primary AEC were isolated from pathogen-free, male Sprague-Dawley rats (200-225 g; for rAEC) or C57/BL6 mice (for mAEC) as previously described (Budinger et al, 2008;DeBiase et al, 2006;Eisenberg et al, 2011). The day of cell isolation is designated as day 0 in culture.…”
Section: Alveolar Epithelial Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Primary AEC were isolated from pathogen-free, male Sprague-Dawley rats (200-225 g; for rAEC) or C57/BL6 mice (for mAEC) as previously described (Budinger et al, 2008;DeBiase et al, 2006;Eisenberg et al, 2011). The day of cell isolation is designated as day 0 in culture.…”
Section: Alveolar Epithelial Cell Isolation and Culturementioning
confidence: 99%
“…Proteins were separated by SDS-PAGE, transferred to nitrocellulose membranes and processed for immunoblotting as previously described (Budinger et al, 2008;Eisenberg et al, 2011). Immunoblots were scanned and quantified using ImageJ (National Institutes of Health, NIH; Bethesda, MD).…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%
“…Stretch of the alveolar basement membrane can exceed this level in patients with respiratory failure who are subjected to positive pressure mechanical ventilation (Vlahakis and Hubmayr, 2005). In cultured primary rat alveolar epithelial cells, we have reported that the interaction between a3-subunit-containing laminins and the cell surface receptor dystroglycan induces signaling that might protect cells from the harmful effects of mechanical stimulation (Budinger et al, 2008). Thus, we hypothesized that in mice the loss of a3 laminin might not only alter the viscoelastic properties of the lung but also disrupt signaling pathways activated by ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that simulate the mechanical stretch of the alveolar wall during VILI utilize different models ranging from pulmonary alveolar epithelial type II cell lines (3,29), primary alveolar epithelial type I and II cells (1,2,15), excised intact lungs (5,6), and living animals (28,32). Although VILI studies with stretched monolayers of cells or ventilated animals can be complicated, stretching precision-cut lung slices (PCLSs) presents additional technical challenges because of the need to fix the slices to a stretchable substrate or hold them in a way that allows deformation without rupture.…”
mentioning
confidence: 99%